Kemampuan Isolataktinomisetes Menghasilkan Enzim yang Dapatmerusak Kulit Telur Nematoda Puru-Akar Meloidogyne spp. - Bambang Rahayu TP; Donny Widianto; Sebastian Margino; Mulyadi Mulyadi (Jurnal Perlindungan Tanaman Indonesia, 2009)
Soil microbes including actinomycetes are known to produce various hydrolytic enzymes and antibiotics that can be used as biological controlling agents nematode. Therefore, surveys conducted in several areas in Yogyakarta, Central Java and East Java, to search for actinomycetes with chitinolytic, proteolytic, and chitino-proteolytic activity. Isolation of Actinomycetes produced 84 isolates, and most was obtained from shrimp head waste (26 isolates). After the selection based on their ability to hydrolyze chitines and protein in the medium, those whith the highest chitin and protein hydrolysis activity, are consecutive PSJ 27, TL 8, and TL 10 isolates. Test results of crude enzyme produced by selected isolates against root-knot nematode eggshell, showed that the isolates that have chitino-proteolytic activity (TL 10), is a highly effective isolate in damage eggshell. There are three types of damage to the nematode eggs. In the young eggs, crude enzyme preparation causing damage on vitelline and chitin layers. In the older eggs, preparation of crude enzyme cause premature hatching.